Model Peningkatan Kinerja Guru MAN 2 Grobogan Berbasis Kepemimpinan dan Disiplin Kerja - Badriyah, Siti; Sulistyo , Heru (Penerbit Goodwood, 2025)
Purpose: This study aims to examine the influence of leadership and work discipline on teacher performance at MAN 2 Grobogan. The issue arises from the need to enhance teacher effectiveness and professionalism through improved managerial and behavioral factors. Leadership and discipline are considered vital variables that impact the quality of education. Research methodology: This quantitative research employs a survey with a causal-comparative design, involving all 38 teachers at MAN 2 Grobogan through total sampling. Data were collected via structured questionnaires and analyzed using multiple linear regression. Results: The results show that both leadership and work discipline significantly affect teacher performance. Leadership plays a vital role in guiding, motivating, and inspiring teachers, while discipline ensures commitment, responsibility, and punctuality in performing teaching duties. The combined effect of both variables demonstrates a strong correlation with performance improvements. Conclusions: The conclusion confirms that strong leadership and disciplined work behavior contribute positively to teacher performance. These findings imply the importance of implementing effective leadership strategies and fostering discipline within the institutional culture. Limitations: This study is limited to one educational institution (MAN 2 Grobogan), which restricts the generalizability of the findings. In addition, the research relies on self-reported data, which may be subject to bias. Contribution: This research adds to the empirical literature on school management by offering evidence-based insights into how leadership and discipline can be leveraged to enhance teacher performance in religious-based public schools like madrasah.